Variations in CO2 fluxes from grass carp Ctenopharyngodon idella aquaculture polyculture ponds - Y Chen (Inter-Research, 2015)
Monthly and diurnal CO2 fluxes at the water-air interface were measured in 3 grass carp Ctenopharyngodon idella polyculture ponds using the closed-chamber method during the farming season from April to September 2013. The results showed that the mean CO2 emission rate from the 3 ponds was 97.8 mg m-2 h-1 (range 50.6 to 151.0 mg m-2 h-1). Apparent seasonal and diurnal variations in CO2 fluxes were observed; the lowest (1.73 mg m-2 h-1) occurred in April and the highest occurred in July and August (212.9 and 181.9 mg m-2 h-1, respectively). The night-time to daytime CO2 emission ratio was <1 (range 0.44 to 0.83) in May during the early part of the farming season. Night-time CO2 emissions in early August were higher than those during the daytime (range 1.06 to 1.37). The night-time to daytime CO2 emission ratios were 0.84 to 1.36 during late September. The CO2 fluxes from the freshwater aquaculture ponds were higher than those of lakes and reservoirs, whereas they were lower than those of marshes in previous studies. The increases in nutrient load and pelagic respiration from feeding the fish were significantly associated with CO2 emissions from the freshwater aquaculture ponds. Freshwater aquaculture ponds in temperate monsoon climate regions contribute an estimated 2.980 million t yr-1 CO2 based on the mean investigated CO2 emission rate, contributing 0.0088% of the current annual global CO2 emissions, and represent a small but previously unquantified CO2 emission source.